Structural, optical, antibacterial, and anticancer properties of cerium oxide nanoparticles prepared by green synthesis using Morinda citrifolia leaves extract - Elderdery, Abozer Y.; Alzahrani, Badr; Alabdulsalam, Abdulrahim A.; Hamza, Siddiqa M. A.; Elkhalifa, Ahmed M. E.; Alhamidi, Abdulaziz H.; Alanazi, Fehaid; Mohamedain, A.; Subbiah, Suresh Kumar; Pooi, Ling Mok (Hindawi Publishing, 2022)
Currently, new advancements in the area of nanotechnology opened up new prospects in the field of medicine that could provide us with a solution for numerous medical complications. Although a several varieties of nanoparticles is being explored to be used as nanomedicines, cerium oxide nanoparticles (CeO2 NPs) are the most attractive due to their biocompatibility and their switchable oxidation state (+3 and +4) or in other words the ability to act as prooxidant and antioxidant depending on the pH condition. Green synthesis of nanoparticles is preferred to make it more economical, eco-friendly, and less toxic. The aim of our study here is to formulate the CeO2 NPs (CeO2 NPs) using Morinda citrifolia (Noni) leaf extract and study its optical, structural, antibacterial, and anticancer abilities. Their optical and structural characterization was accomplished by employing X-ray diffractography (XRD), TEM, EDAX, FTIR, UV-vis, and photoluminescence assays. Our CeO2 NPs expressed strong antibacterial effects against Gram-positive S. aureus and S. pneumonia in addition to Gram-negative E. coli and K. pneumonia when compared with amoxicillin. The anticancer properties of the green synthesized CeO2 NPs against human acute lymphoblastic leukemia (ALL) MOLT-4 cells were further explored by the meticulous study of their ability to diminish cancer cell viability (cytotoxicity), accelerate apoptosis, escalate intracellular reactive oxygen species (ROS) accumulation, decline the mitochondria membrane potential (MMP) level, modify the cell adhesion, and shoot up the activation of proapoptotic markers, caspase-3, -8, and -9, in the tumor cells. Altogether, the outcomes demonstrated that our green synthesized CeO2 NPs are an excellent candidate for alternative cancer therapy.